Performance and stability of ridge gourd (Luffa acutangula (L.) Roxb. var. Arka Prasan) under integrated nutrient management in Telangana - Shailaja, Gogu; Pagadala, Sai Priyanka; Mandava, Hemalatha; Dulam, Shivaraj; Kadarla, Chaitanya; Chittem, Vara Prasad; Shaik, N Meera; Rajneesh, Kumar (Plant Science Today, 2026)
The increasing demand for organically grown vegetables necessitates adopting sustainable nutrient management practices. This four-year study (2021–24) evaluated 7 Integrated Nutrient Management (INM) strategies on ridge gourd (Luffa acutangular (L) Roxb. cv. Arka Prasan). Key parameters assessed included Days to First Harvest (DFH), Fruit Yield per Hectare (FY/HA), Average Fruit Weight (AFW) and Benefit-Cost Ratio (BCR). Statistical analyses using Analysis of Variance (ANOVA), the Eberhart & Russell stability model and Principal Component Analysis (PCA) revealed significant treatment differences. Application of enriched compost at 2.5 t/ha (T₆) consistently outperformed other treatments, recording the highest mean yield (21.83 metric tonne/ha) and BCR (1.958). This treatment also showed perfect stability, with a deviation from regression (S²di) of 0.000 for both yield and profitability, confirming reliability across environments. While T₆ was superior for yield and profitability, treatment T₂ (biofertilizer consortium + compost at 2.5 t/ha) was identified as the earliest to harvest. The findings suggest that enriched compost at 2.5 t/ha is the most effective, stable and economically viable option for ridge gourd cultivation and is strongly recommended for farmer adoption.